Gingival smile correction through the increase in clinical crown using the flapless technique: An integrative review (Research, Society and Development, 2021)
Objective: This integrative review aimed to evaluate how current scientific research on the correction of gingival smile by increasing the clinical crown using a “flapless” technique and comparing the results with the conventional technique. Material and methods: A search was conducted in ten electronic databases as initial sources of study. The search resulted in 404 articles, of which nine were considered eligible. Results: Clinical and scientific evidence has highlighted that the increase in the clinical crown with the “flapless” technique is a viable surgical alternative for the correction of the gingival smile or for the correction of the disharmonious shape of the gingival line. The benefits of this procedure are less bleeding, greater patient acceptance, immediate effective result, low morbidity, without the need for sutures, rapid healing and good stability of the gingival mage. Conclusions: The etiological factors and indications must be carefully analyzed in order to carry out an adequate planning and obtain success in the procedure.